Genotype analysis of enterotoxin H-positive Staphylococcus aureus strains isolated from food samples in the Czech Republic - Růzicková, Vladislava; Karpísková, Renata; Pantůcek, Roman; Pospísilová, Markéta; Cerníková, Pavla; Doskar, Jirí (International journal of food microbiology, 2008)
Twenty-eight enterotoxin H-positive Staphylococcus aureus strains isolated from food samples collected in eleven districts of the Czech Republic between 2000 and 2005 were genotypically characterized by pulsed-field gel electrophoresis (PFGE) profiling, spa gene polymorphism analysis, enterobacterial repetitive intergenic consensus sequence-based PCR (ERIC-PCR) fingerprinting and prophage carriage detection. These strains accounted for about 21% of the food-derived, staphylococcal enterotoxin (SE)-positive isolates. One strain, detected in feta cheese, was implicated in a case of enterotoxinosis. Sixteen of the twenty-eight isolates carried the seh gene alone. The remaining twelve strains harbored the seh gene in combination with other enterotoxin genes, most often the seg and sei genes, followed by the sea, seb, sec and sed genes. Comparison of various genomic profiles resulted in the determination of twenty genotypes designated G-1 to G-20. Two new, to date not defined, spa types (t2000 and t2002) were identified in one strain isolated from raw meat and two strains obtained from prepacked pizza. Evidence has been given that the seh-positive S. aureus isolates from foodstuffs did not originate from a single source or a common ancestor.
Keywords: DNA fingerprinting; genotyp; DNA, Bacterial; potravinářská mikrobiologie; DNA Fingerprinting; Genotype; Česká republika; Food Microbiology; Enterotoxins; stafylokoková otrava přenesená potravou; Czech Republic; polymorfismus genetický; Staphylococcus aureus; DNA bakterií; kontaminace potravin; Polymorphism, Genetic; Humans; Food Contamination; Staphylococcal Food Poisoning; pulzní gelová elektroforéza; enterotoxiny; Electrophoresis, Gel, Pulsed-Field; lidé